Agile manufacturing practices for new product development: industrial case studies. Issue 4 (3rd May 2016) - Leite, Marco; Braz, Vanessa
Abstract : Purpose: – For decades multiple management philosophies directed toward lean production and mass were assumed as to respond to process inefficiencies and rampant consumerism, optimizing operation costs. However, new customization and flexible productions philosophies have been gaining ground in some industries, such as the agile manufacturing. From a literature review that addresses the history of this philosophy, it is clear that agile manufacturing is not fully comprehended, with very scarce information about practical cases. The paper aims to discuss these issues. Design/methodology/approach: – In this paper the authors describe an exploratory methodology approach, with three semi-structured case study interviews. The goal is to study which of agile manufacturing practices are being applied in the studied companies and what is the perceived effect that these have on operational performance. Since most of these companies develop highly customized products, the role of agility on new product development can have a huge impact on their operational performance. Findings: – Agile manufacturing is not yet a widespread philosophy of managing for the companies studied, being virtually unknown as a global concept. However, it was found that many of the practices of agile manufacturing are already implemented in these companies without association with this philosophy. It was also concluded, by the finding through respondents opinions, that agile practices contribute positively to the studied companies operating performance. Originality/value: – The novelty of this research derives from observation of agile manufacturing practices in SMEs. This research is useful to SMEs implementing agile manufacturing principles.